Feasibility of spiral enteroscopy in Japanese patients: Study in two tertiary hospitals. Issue 4 (5th December 2012) - Yamada, Atsuo; Watabe, Hirotsugu; Oka, Shiro; Kogure, Hirofumi; Imagawa, Hiroki; Kobayashi, Yuka; Suzuki, Hirobumi; Watari, Ikue; Aoyama, Taiki; Isayama, Hiroyuki; Yamaji, Yutaka; Fujishiro, Mitsuhiro; et al.
Abstract : Background and Aim: Despite recent advances in enteroscopy, such as balloon enteroscopy, accessing the small intestine remains challenging. Spiral enteroscopy is a novel technique in which an endoscope is fitted with a rotating overtube that has a soft spiral fin at the tip. Whereas spiral enteroscopy is beginning to be carried out in Western countries, it is not common in many Asian countries. The aim of the present study was to evaluate the efficacy and safety of spiral enteroscopy in Japanese patients. Methods: We prospectively conducted spiral enteroscopy in patients with suspected or known small bowel disease. All procedures were carried out using a spiral overtube. The main outcome measurements of the study were diagnosis rate, endoscopic intervention rate, and complication rate. Results: Thirty‐two patients underwent spiral enteroscopy. Spiral enteroscopy diagnosed 16 patients (50%) with small intestinal lesions, including six malignant lymphomas (19%), three erosions or ulcers (9%), three polyps (9%), two angioectasias (6%), one carcinoma (3%), and one submucosal tumor (3%). Additionally, four patients underwent endoscopic interventions (13%). Mallory‐Weiss syndrome occurred in one patient (3%). No perforation occurred in any patient (0%). Conclusions: Our initial experience of spiral enteroscopy suggests that it can be introduced safely, but it is relatively invasive and technically demanding. More experience is needed to conduct spiral enteroscopy easily and safely.